Association of Mucoid Degeneration of the Anterior Cruciate Ligament at MR Imaging with Medial Tibiofemoral Osteoarthritis Progression at Radiography: Data from the Osteoarthritis Initiative - Kwee, Robert M.; Hafezi-Nejad, Nima; Roemer, Frank; Zikria, Bashir A.; Hunter, David J.; Guermazi, Ali; Demehri, Shadpour (Radiology, 2018)
Purpose To determine whether anterior cruciate ligament (ACL) mucoid degeneration in participants with or at risk for osteoarthritis is associated with longitudinal risk of radiographic progression of medial tibiofemoral compartment joint space loss (JSL). Materials and Methods Baseline demographic, clinical, radiographic, and Magnetic Resonance (MR) Imaging Osteoarthritis Knee Score (MOAKS) data were evaluated in 600 participants from the Osteoarthritis Initiative database. Two blinded musculoskeletal radiologists independently evaluated baseline MR images for ACL mucoid degeneration. Multiple logistic regression was used to investigate the association between ACL mucoid degeneration at MR imaging and JSL progression at radiography, defined as a minimum joint space width decrease greater than 0.7 mm (48 months; cutoff according to mean and standard deviation of 1-year minimum joint space width changes in 90 knees of reference group). Stratified analysis was performed based on baseline cartilage surface damage. Results Knees with ACL mucoid degeneration showed a greater proportion of JSL progression compared with knees with a normal ACL (64% vs 47%; P = .004). After adjustment for all demographic, clinical, radiographic, and MOAKS variables, ACL mucoid degeneration was not statistically significantly associated with JSL progression in the entire cohort (adjusted odds ratio, 1.66; 95% confidence interval: 1.00, 2.77; P = .051). In subgroup analysis, ACL mucoid degeneration was statistically significantly associated with JSL progression in participants with less baseline cartilage surface damage (maximum cartilage surface loss of ≤75% in all subregions [P = .015] and ≤4 of involved subregions with cartilage surface loss [P = .028]). Conclusion ACL mucoid degeneration in participants with or at risk for osteoarthritis is associated with progression of medial tibiofemoral compartment JSL in knees with less baseline cartilage surface area damage. © RSNA, 2018 Online supplemental material is available for this article.
EVALuna2:35359